Preservation of historical records - National Research Council (U.S.). Committee on Preservation of Historical Records (Washington, D.C. : National Academy Press, 1986)
"The National Archives is the repository for permanently valuable documents of various federal government agencies. Concerns exist about the condition of some stored paper records because of the increasing quantities that must be handled and the deteriorating condition of some of them. Various methods of preserving paper records were examined, and alternative actions for preserving the original documents or retaining more permanently the information contained in them were assessed. The accessibility requirements of the Archives retrieval system limit the acceptable preservation alternatives for most of the at-risk holdings to photocopying and photographic storage. Environmental effects are discussed, and standards for potentially dangerous airborne contaminants in the Archives storage areas are developed. Continued monitoring of potentially high-risk records is necessary so that timely corrective action can be taken."--Page xv.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Manuscripts -- Conservation and restoration; Archival materials -- Conservation and restoration; History -- Sources -- Conservation and restoration; Archives; Manuscripts as Topic; Manuscrits -- Conservation et restauration; Documents d'archives -- Conservation et restauration; Histoire -- Sources -- Conservation et restauration; Archives; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Archival materials -- Conservation and restoration; History -- Sources -- Conservation and restoration; Manuscripts -- Conservation and restoration; Archivalien; Konservierung; Restaurierung; Archival materials -- Conservation and restoration; History -- Sources -- Conservation and restoration; Manuscripts -- Conservation and restoration; Electronic book